I know, therefore I am healthier? The role of education in health-related behaviors (2019)
To know how better economic conditions impact health-related choices is critical when formulating public policies that aim at improving the population¿s health, both in terms of outcomes and habits. Through the use of two national surveys, we investigate the effect of one additional year of schooling on the amount of time of physical activity done per week, and on the servings consumed of fruits and vegetables per day, in urban Colombia. Furthermore, intending to find causal links, we exploited as a source of exogenous variation a change in regulation concerning basic education implemented in the 1970s, in a 2SLS framework. Our results suggest that higher levels of education have a positive impact on food consumption habits, and on the undertaking of physical activity, especially when it is done for leisure. Conversely, transport-motivated physical activity is unaffected by higher educational attainment, which points to the presence of protective factors in low SES individuals. For the consumption part, we find that access is a necessary condition for individuals to make healthy diet choices.